Mendorong Inovasi Produk Dan Daya Saing Global UMKM Kreatif Melalui Adopsi Teknologi Artificial Intelligence - Gumilar, Angga; Mulyana, Asep Endri (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2025)
Tasikmalaya's craft MSMEs have great economic potential, but their competitiveness is hampered by limited technology and product innovation. This study aims to analyze the effect of AI adoption on product innovation and the competitiveness of creative MSMEs, and to examine the role of product innovation as a mediator in this relationship. The study used a quantitative approach with a survey method of creative MSMEs in Tasikmalaya. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The results show that AI adoption has a significant positive effect on product innovation, and product innovation has a significant effect on competitiveness. In addition, product innovation is proven to partially mediate the relationship between AI adoption and MSME competitiveness. These findings enrich the application of the Technology–Organization–Environment (TOE) framework by emphasizing the strategic role of product innovation as a mechanism for technological transformation towards competitive advantage. Practically, the research findings emphasize the importance of improving digital literacy, AI-based training, and developing an innovation ecosystem that supports local MSMEs to compete in the global market. This study provides theoretical and practical contributions to strengthening the transformation of a green creative economy based on local resources.